Effects of Exercise Aerobic Endurance Against Shooting Ability - Nailatul Fadilla; Umar - (Performa, 2019)
This study aims to see the extent of the effect of aerobic endurance training on shooting ability, with quasi-experimental research (quasi-experimental), conducted pre-test and post-test to collect quantitative data. The population in this study were all maleclass athletes youth, totaling 12 people. The sampling technique in this study used purposive sampling technique, the sample in this study amounted to 7 athletes, conducted for 3 weeks (18 meetings). The research instrument was a scoring test in accordance with ISSF (international regulationsInternational Shooting Sport Faderation). Data analysis techniques in this study were to use data normality test and T-Test test. The results of research and hypothesis testing can be concluded that there is a significant effect of aerobic endurance training methods on shooting ability. Regular aerobic endurance training allows athletes to better regulate their heart rates. This finding may be useful for trainers, because it can add references to the form of training in improving achievement. The application of aerobic training in the process of shooting practice can improve the ability to shoot athletes.